Challenges and initiatives in teaching science and mathematics in rural area: a case study / Azwan Ahzran Perman - Perman, Azwan Ahzran (2021)
Education is one of the fundamental needs of focus for a developing country. Within geographical factors, urban and rural areas seem to vary in their challenges in providing education. One of the remotest places in Sabah, which is Pulau Banggi, sets as the location of this case study, where specifically the school of SK Sabur is the main focus. This study attempted to understand the challenges and initiatives of teachers for teaching science and mathematics in a rural school. Rural elementary school is in itself a challenge for teachers. According to facts, rural schools generally have inferior equipment and infrastructure than urban schools mainly due to location and funding. Teaching Science and Mathematics can be even more challenging than non-technical ones there. Being a qualitative study, it has collected data from a descriptive case study, a semi-structured interview, and observation. Through triangulation of the data and thematic analysis of the transcriptions, the study found the following themes: (I) Governmental role in the rural area, (II) personal sacrifices, and (III) local-based innovation for teaching. The study emphasizes that the government must continue improving ways to mitigate the challenges that teachers face in teaching Science and Mathematics in rural schools as well as the local rural infrastructure to ensure the delivery of quality education across all areas of the country. Future studies should also include challenges teaching in the rural area during Covid-19-lockdown and restricted movement phases.